Anxiety Sensitivity and Negative Affect: Transdiagnostic model for anxious and depressive symptoms - Toro Tobar, Ronald Alberto (2019)
The aim of the study was to identify the predictive role of anxiety sensitivity (SA) and negative affect (AN) on anxiety and depression, a relationship that has not been analyzed in detail. A multivariate correlational study was carried out with structural equations. The sample included 506 participants (M = 31.96, SD = 11.26 years). Significant correlations were reported between the transdiagnostic variables and the symptoms, with wide differences once the AN was controlled. The regression coefficients showed a high predictive capacity of SA and AN, especially with anxiety. In a structural model, a favorable adjustment without evidence of AN mediation in the SA and symptoms. The possibilities of AN and SA are discussed as second-order variables that suggest a higher order model.